فعالية الأنثروبولوجيا الطبية في فهم الصحة والمرض - رابحي, اسماعيل; حوحو, عائشة (Changement Social, 2018)
يمثل المثل الشعبي جزءاً هاما من التراث الثقافي غير المادي الذي يتناول في مضامينه ومحتوياته العديد من التفسيرات والدلالات الثقافية–الاجتماعية التي تلخص تجارب الشعوب في تنظيم حياة الأفراد والجماعات في جميع أبعادها ومستوياتها. ومن أكثر الأمثلة الشعبية المتداولة في أي ثقافة نجد ما يتعلق بمسائل المرض وطرائق العلاج و الوقاية ، وصحة الأبدان وقوة الأجساد وغيرها من مظاهر الخطورة والألم والخوف من الموت والمرض، وهو ما نسعى إليه خلال هذا المقال الذي سنتناول فيه نموذج المثل الشعبي كأحد إسهامات الأنثروبولوجيا الطبية في فهم قضايا الصحة والمرض. The popular proverb Constitute an important part of the intangible cultural heritage, whose contents Includes many interpretations and cultural-social connotations that summarize peoples' experiences in organizing the lives of the individuals and the communities in all its dimensions and levels. Among the most popular proverbs in any culture are the issues of disease, methods of treatment and prevention, the strength of bodies and other manifestations of danger and pain and fear of death and disease. This is what we seek in this article in which we will discuss the model of popular proverbs as one of the fundamental contributions of medical anthropology to understanding health and disease issues.